Pengaruh NPF, FDR, dan BOPO terhadap tingkat bagi hasil deposito mudharabah: ROA sebagai variabel moderating - Damayanti, Aninda Eva Riri Indah; Annisa, Arna Asna (Nur Science Institute, 2021)
This study aims to analyze the effect of non-performing financing, financing to deposit ratio, and operational costs and operational income on the profit-sharing rate of mudharabah deposits with return on asset as a moderating variable. This research is quantitative research with data panels. The population in this study was 14 Islamic Commercial Bank in Indonesia for the period 2015-2019. The sample selection used the purposive sampling method. The analysis technique used is multiple linear regression analysis. The results found that non-performing financing and operational costs and operational income have a negative effect on the profit-sharing rate of mudharabah deposits. However, the financing to deposit ratio has a positive effect on the profit-sharing rate of mudharabah deposits. Return on assets does not moderate the non-performing financing and financing to deposit ratio variable but does moderate operational costs and operational income variable on the profit-sharing rate of mudharabah deposits.